Toxicological evaluation of pesticide impact "threshold" for different types of plants - Толошна, А.А.; Білик, Т.І. (Proceedings of National Aviation University (archive), 2009)
It was investigated influence of the not licensed in Ukraine pesticide «Barier» on the indexes of growth and development of three kinds plants: pea, lettuce and corn. It was ascertain phytotoxic effect and the pesticide effective concentration EK50. According to received information, a pea is most sensible to influence of pesticide, in that time as a corn tests selective influence, and the most impact appeared on the lettuce plants.